Comparison of parental and practitioner's acceptance for dental treatment under general anaesthesia in paediatric patients - Yassamin Djalali Talab; Margrit-Ann Geibel (BMC, 2023)
Abstract Background Practitioner's knowledge and parental perspectives on dental general anaesthesia (GA) have been surveyed separately in the past. But in daily routine both need to collaborate for the benefit of the child. The aim of this paper was to compare parental and practitioner's acceptance of GA with special focus on identifying factors which influence their differences in decision making. Methods Questionnaires were conducted among 142 participants in a specialized paediatric dental clinic in Germany from February 2020 to February 2021. 51 German practitioners from private practices and clinics participated. Data collection included: age, gender, experience with GA, fear of GA, risk evaluation and indications for GA. Results There were no gender related differences in decision making. Emotional factors are present in parents of younger children. Parents are more likely to express fear and uncertainty regarding GA than dentists. Prior experience with GA significantly decreases fears in GA for parents. Both agree that extent of the treatment and low compliance are a suitable indication for GA. Dentists are more likely to accept GA due to a mental disability than parents. Parents were more likely to accept GA than dentists when multiple extractions were needed (regardless of compliance) or acute pain was present. Conclusions A significant divergence in risk evaluation, acceptance and decision-making could be found in parents compared to dentists. Influencing factors are previous experience, younger age of the child, lack of knowledge and indication for GA.